667 Virtual Learning During The COVID-19 Pandemic Amongst Medical Students in The United Kingdom. (4th May 2021) - Jayawardena, O; Toh, S; Fowler, H; Fok, M; Clifford, R
Abstract: Introduction: Throughout the COVID-19 pandemic medical education has predominantly been delivered through virtual learning (VL). This survey was conducted to evaluate the effectiveness of VL amongst medical students in the UK. Method: An online anonymised SurveyMonkey© survey was distributed through social media amongst UK medical students. Results: There were 142 completed surveys, 96.5% of students engaged in some form of VL during the pandemic, compared to 57.8% prior to the pandemic. The most frequently used method to deliver teaching was interactive online lectures (74.7%). The students perceived small group online teaching sessions to be the most effective delivery method (weighted average 7.4/10) followed by interactive online lectures (7.4/10). The least effective teaching method was online lecture notes (5.3/10). Accessibility to coursework (8.6/10) and enhanced flexibility (8.4/10) were considered to be the biggest advantages of VL. Overall, 44% of students felt VL had a negative impact on their learning, with 23% of students considered to have failed to meet the learning objectives set out in these sessions. Conclusions: Beyond the COVID-19 pandemic VL will continue to play a role in medical education. However, there is room for improvement in both delivery and engagement to improve student experience and satisfaction.